Effects of selective water withdrawal schemes on thermal stratification in Kouris Dam in Cyprus - Ma, Shengwei; Kassinos, Stavros; Fatta-Kassinos, Despo; Akylas, Evangelos (My University, 2008)
Thermal stratification and its seasonal variations in Kouris Dam in Cyprus were simulated, and the impact of five different water withdrawal schemes was studied, using the 2-D, laterally averaged CE-QUAL-W2 reservoir model. Based on the model simulations, it was found that the thermal stratification of the reservoir is significant for most of the year. Most importantly, a complete mixing of the water column, triggered by seasonal variations in meteorological conditions, occurs in late-January. Predicted thermal stratification and water temperature profiles in the reservoir are noticeably affected by water withdrawal schemes. It was found that deep-water withdrawals tend to facilitate heat transfer in the water column and deepen the water mixing layer (epilimnion), especially from September to the following January. These study results suggest that it is prudent for Kouris Dam to integrate selective water withdrawal schemes into reservoir management by using the water withdrawal effects on thermal stratification for different water quality management strategies.
Keywords: CE-QUAL-W2; Kouris Dam; Numerical simulation; Selective withdrawal; Stratification